Cell-type-specific tuning of Cav1.3 Ca2+-channels by a C-terminal automodulatory domain - Scharinger, Anja; Eckrich, Stephanie; Vandael, David H.; Schönig, Kai; Koschak, Alexandra; Hecker, Dietmar; Kaur, Gurjot; Lee, Amy; Sah, Anupam; Bartsch, Dusan; Benedetti, Bruno; Lieb, Andreas; et al. (Frontiers in Cellular Neuroscience, 2015)
Cav1.3 L-type Ca2+-channel function is regulated by a C-terminal automodulatory domain (CTM). It affects channel binding of calmodulin and thereby tunes channel activity by interfering with Ca2+- and voltage-dependent gating. Alternative splicing generates short C-terminal channel variants lacking the CTM resulting in enhanced Ca2+-dependent inactivation and stronger voltage-sensitivity upon heterologous expression. However, the role of this modulatory domain for channel function in its native environment is unkown. To determine its functional significance in vivo, we interrupted the CTM with a hemagglutinin tag in mutant mice (Cav1.3DCRDHA/HA). Using these mice we provide biochemical evidence for the existence of long (CTM-containing) and short (CTM-deficient) Cav1.3 α1-subunits in brain. The long (HA-labeled) Cav1.3 isoform was present in all ribbon synapses of cochlear inner hair cells. CTM-elimination impaired Ca2+-dependent inactivation of Ca2+-currents in hair cells but increased it in chromaffin cells, resulting in hyperpolarized resting potentials and reduced pacemaking. CTM disruption did not affect hearing thresholds. We show that the modulatory function of the CTM is affected by its native environment in different cells and thus occurs in a cell-type specific manner in vivo. It is required to stabilize gating properties of Cav1.3 channels required for normal electrical excitability.